Pengaruh kesediaan dalaman, strategi pembangunan dalaman, strategi latihan dan strategi menghafal Al-Quran terhadap pencapaian subjek Hifz Al-Quran pelajar tahfiz di Malaysia - Intan Zakiah, Jamaluddin (2018)
The achievements of tahfiz students are variable. Most studies in the field of tahfiz education concentrate on the external aspects such as techniques and methods of memorization, teaching and syllabus, environmental factors, facilities and institutions. However, not much researches were done focusing on the quality or characteristics of the students. The objectives of this study focus on the internal readiness, internal development strategies, training strategies, and Qur’an memorization strategies towards the performance. The study used a quantitative approach through questionnaires and supported by qualitative data using interviews and observation with the students and lecturers. A sample of 298 diplomas students from JAKIM tahfiz institutions were chosen using stratified random methods. Questionnaires were adapted from previous studies. Overall, descriptive data analysis showed students achievement were dominance at the outstanding levels compared to other achievement levels. The study found that the internal readiness (r = 0.167, p <0.01) and the Qur’an memorization strategy (r = 0.139, p <0.01) had significant relationship with the performance in the Ḥifẓ al-Qurʾan subject. While regression analysis showed that the component of internal readiness is the key predictor of achievement. The self-efficacy elements in the internal readiness components could predicts 8.9% of the achievement variances. While the findings of interview data and the observational had described the elements in the four variables in more details. The findings of this study illustrate that the internal readiness and Quran memorization strategy are the two most important characteristics of the tahfiz students. However, internal development strategies and training strategies component should also be addressed and have important roles. This study implies that developing all four characteristics in the students is fundamental for the improvement of the quality of the ḥuffaẓ generation. Its findings could also give specific guidances to the practitioners, policy makers, implementers of Tahfiz institution and science corpus.